Synthesis of Natural Deep Eutectic Solvent from EFB Waste and Used Cooking Oil for Cathode Recovery - Hadrian Hafiz; Khansa Khairunisa Karyani; Muhammad Fiqri Aulia Rahman; Sawbil Sabri; Windri Putri Lestari; Ferdinand Hidayat (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study develops a biomass-derived natural deep eutectic solvent (NADES) by combining potassium carbonate-rich oil palm empty fruit bunch (EFB/TKKS) ash as the hydrogen bond acceptor, and polyol-rich used cooking oil as the hydrogen bond donor for cobalt recovery from spent lithium-ion battery cathodes. The novelty of this work lies in converting two abundant local waste streams into a reusable green leaching medium for battery recycling. The HBA and HBD precursors were prepared through ash extraction, used-oil purification, and hydroxylation, followed by thermal mixing at molar ratios of 1:1, 1:2, and 2:1. The products were evaluated using density, viscosity, water-solubility, FTIR, GC-MS, AAS, UV-Vis, and qualitative cobalt confirmation tests. The 1:2 ratio produced the most stable homogeneous NADES, with a density of 0.8895 g/mL and viscosity of 55.57 mPa·s. FTIR and GC-MS analyses confirmed hydroxyl-bearing components and hydrogen-bond interactions that support eutectic solvent formation. During cobalt recovery, the first three regeneration cycles produced apparent cobalt-containing solid recovery values of 53.41%, 51.11%, and 49.30%, with solid recovery yields of 99.82%, 95.52%, and 92.15%, respectively. These findings indicate that EFB- and used-cooking-oil-derived NADES is a promising waste-based solvent platform for more sustainable lithium-ion battery cathode recycling, although further optimization is required to improve cobalt recovery efficiency and long-term solvent stability.